Multi-site medical record review for validation of intentional self-harm coding in emergency departments - Barbara A. Gabella; Beth Hume; Linda Li; Marianne Mabida; Julia Costich (BMC, 2022)
Abstract Background Codes in the International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM), are used for injury surveillance, including surveillance of intentional self-harm, as they appear in administrative billing records. This study estimated the positive predictive value of ICD-10-CM codes for intentional self-harm in emergency department (ED) billing records for patients aged 10 years and older who did not die and were not admitted to an inpatient medical service. Methods The study team in Maryland, Colorado, and Massachusetts selected all or a random sample of ED billing records with an ICD-10-CM code for intentional self-harm (specific codes that began with X71-X83, T36-T65, T71, T14.91). Positive predictive value (PPV) was determined by the number and percentage of records with a physician diagnosis of intentional self-harm, based on a retrospective review of the original medical record. Results The estimated PPV for the codes' capture of intentional self-harm based on physician diagnosis in the original medical record was 89.8% (95% CI 85.0-93.4) for Maryland records, 91.9% (95% CI 87.7-95.0) for Colorado records, and 97.3% (95% CI 95.1-98.7) for Massachusetts records. Conclusion Given the high PPV of the codes, epidemiologists can use the codes for public health surveillance of intentional self-harm treated in the ED using ICD-10-CM coded administrative billing records. However, these codes and related variables in the billing database cannot definitively distinguish between suicidal and non-suicidal intentional self-harm.